Explosion resistant design of offshore structures - Brewerton, R. (Technical note (Fire and Blast Information Group) ;, 1996)
"Where gas explosions represent a credible risk, platform topsides have to be designed to withstand explosion loading. There are two aspects to consider: firstly loading on the structure and secondly loading and effect on equipment. This Technical Note deals principally with the first aspect but is also relevant to the second because the performance of the structure, e.g. deflection and acceleration, affects the equipment mounted on it. It is also relevant to the evaluation of the strength and deformation capacity of the equipment items themselves, e.g. pipes and vessels. This Technical Note covers both design of new platforms and reassessment of existing structures."--Knovel.